ChemInform Abstract: Copper(II)‐Promoted, One‐Pot Conversion of 1‐Alkynes with Anhydrides or Primary Amines to the Respective 2, 5‐Disubstituted Furans or Pyrroles under Microwave Irradiation Conditions. Issue 15 (24th March 2016) - Lee, Hyejeong; Yi, Yeonhui; Jun, Chul‐Ho
Abstract: The method allows an efficient approach to the desired heterocycles within a short time.